Differentiating peripheral cholangiocarcinoma in stages T1N0M0 and T2N0M0 from hepatic hypovascular nodules using dynamic contrast-enhanced MRI - Shihong Li (Nature Portfolio, 2017)
Abstract Because cholangiocarcinoma shows no specific clinical signs or symptoms and presents with non-specific biological and tumor markers in the early stages, MRI findings often lack typical features before this lesion becomes symptomatic and might be mistaken for other liver lesions. An evaluation of relevant radiological findings in nodular cholangiocarcinoma (≤3 cm) in stages T1N0M0 and T2N0M0 is urgently needed. In our study, we compared two groups of liver hypovascular nodules and found that a distinct margin and enhanced area/nodule size >2/3 in the delayed phase were more frequently observed in cholangiocarcinoma cases than in metastatic nodule cases in which markedly high signal intensity on T2WI was common (p < 0.05). The results also revealed that in the both the portal and delayed phases, an enhanced area/nodule size >2/3 favored cholangiocarcinoma, whereas the presence of regional markedly higher SI on T2WI favored benign nodules. Furthermore, signs of peripheral washout in the delayed phase only appeared in cholangiocarcinoma cases.